Do Ostriches Worry Less? Information Avoidance and Retirement Worry - Mindy Joseph; Han Na Lim; Derek Lawson; Maurice MacDonald; Ansley Chua (Journal of Financial Therapy, 2024)
The demand for information and its usefulness is well documented and found to be driven by factors such as curiosity, the pursuit of knowledge, or increased economic utility. However, the usefulness of information can be offset by avoidance responses. This study investigated the relationship between the practice of information avoidance and retirement worry based on theoretical support from the transactional theory of stress and coping. Specifically, this study focused on avoiding information related to retirement savings needs. Results showed that as respondents increased avoidance behaviors, they were more likely to report no retirement worry relative to each of the higher reported levels of retirement worry. These findings support increased attention to avoidance behaviors by financial planners, therapists, and counselors as it can influence, or possibly mask, the emotional well-being of their clients. The study’s insights can be used in various contexts, e.g., communicating financial information, making recommendations, or developing client coping strategies.
Keywords: information avoidance; retirement worry; transactional theory of stress and coping